Evaluation and comparison of trends in insulin utilization for period 2019-2023 in Skopje - Anife Shabani; Zorica Naumovska; Iskra Sadikarijo-Pecijareva; Zoran Sterjev (Makedonsko Farmacevtski Bilten)
Diabetes affects an estimated 537 million adults aged 20–79 globally, with prevalence projected to rise to 643 million by 2030 and 783 million by 2045. In North Macedonia, data from 2018–2021 show a growing number of individuals with diabetes, with 6.6% of the population affected in 2021. This study evaluates insulin consumption trends in Skopje, Republic of North Macedonia, from 2019 to 2023, comparing local patterns with global data. Using a retrospective design, insulin utilization data were obtained from the national e-health system, My Term (MojTermin). Analysis of the National Register for Diabetes Mellitus confirmed an increasing prevalence of diabetes in Skopje during the study period. A significant decline of nearly 50% in the use of human bolus insulin was observed, while long-acting insulin analogs have increased utilization. Insulin glargine (Lantus) was the most widely used basal insulin in 2021, coinciding with the introduction of its biosimilar, Abasaglar. Additionally, insulin detemir (Levemir) is being progressively replaced by insulin degludec (Tresiba), which offers a superior therapeutic profile and a reduced risk of hypoglycemia. In 2021, Rizodeg, an innovative insulin combination, was introduced to the Macedonian market. These findings reflect a global trend of declining human insulin use and increasing adoption of long-acting insulin analogs, driven by their improved efficacy and safety profiles. The transition towards newer insulin formulations highlights a shift in diabetes management aimed at improving patient outcomes and reducing diabetes-associated complications.